Legal Construction of Crypto Assets as Objects of Fiduciary Collateral - Mulyani, Sri; Mariyam, Siti; Trung Le, Hieu Hong (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
Crypto assets have become the commodities traded on the Futures Exchange. Based on the data from the Ministry of Trade, the number of crypto asset investors in Indonesia will reach 11 million people by the end of 2021. The high level of crypto investment and public interest in crypto as a digital asset provide excellent opportunities for Indonesia's digital industry and economic growth. This research will discuss the use of crypto assets as objects of fiduciary collaterals and the legal framework used as a legal basis for crypto assets subject to fiduciary collaterals. The research methodology is normative juridical applied using a comparative approach to the laws in Indonesia and Vietnam because the rules regarding crypto assets in Vietnam are clearer. The data collected were secondary data, and the they were analysed using qualitative data analysis. The results of the study show that crypto assets are intangible movable objects that have economic value and can be transferred due to an agreement through each user's account so that conceptually crypto assets can be used as fiduciary collateral objects. However, considering that crypto assets are digital currencies cannot be predicted, legal protection for creditors holding crypto asset collaterals is still weak. In addition to the absence of regulations that specifically regulate crypto assets that can be used as objects of fiduciary collateral, there are also difficulties in execution, so there is a need for a construction legal umbrella that regulates crypto assets to be used as fiduciary collateral objects.